Microbial production of value-added products from wood hemicellulose prehydrolysate - Samavi, Mahdieh (2020)
Hemicellulose, the second most abundant polymer in nature, has the great potential to be used for the production of biochemicals under the concept of biorefining. As hemicellulose is watersoluble, it can also be easily obtained by the pre-hydrolysis of wood prior to the pulping processes such as Kraft delignification or during the production of dissolving pulp. Utilization of these byproduct streams can play an important role in the development of a circular bioeconomy as it helps in maintaining the materials and resources for a long period instead of disposing it as waste. In the biochemical conversion platform for biorefineries, it is crucially important to use all fermentable sugars of lignocellulosic biomass including both hexose (C-6) and pentose (C-5) sugars. The overall objective of this study was to produce bioplastic building blocks from hemicellulose streams. The specific objective of this work was to investigate the possibility of using wood-based hemicellulose for microbial production of value-added biochemicals including microbial oil, biopolyol and poly-γ-glutamic acid. The hemicellulose pre-hydrolysate used in this study was produced by a proprietary pretreatment process. Composition analysis of the hemicellulose prehydrolysate indicated that it had 143.89 ± 1.28 g/L of xylose along with smaller quantities of sugars like glucose and arabinose. Bioconversion of hemicellulose sugar to microbial oil is one possible way to valorize this industrial side stream. An oleaginous yeast Cryptococcus curvatus (ATCC 20509) was selected for this bioconversion as it is known to accumulate high content of lipids and is able to grow on complex lignocellulosic hydrolysates/pre-hydrolysates even in the present of impurities. Initially, the effect of xylose concentration and carbon to nitrogen ratio were investigated in order to maximize the lipid accumulation. The robust yeast strain used was able to produce 13.78 g/L of cell biomass and 5.13 g/L of lipid after 164 hr of fermentation using poplar wood pre-hydrolysate without detoxification. The obtained microbial oil was characterized to identify its fatty acid profile. Oleic acid (45.86 ± 0.69 wt%) was found to be the main fatty acid present. This fermentation was scaled up in a batch bioreactor with 1 L capacity. 16.54 ± 0.65 g/L of cell biomass and 6.97 ± 0.58 g/L of lipid were obtained in the reactor which had better control of environmental conditions. The microbial oil produced was then used as feedstock for production of bio-based polyol which has many applications in polymer industry and importantly serves as a precursor for polyurethane production. The bio-polyol was produced using a two-step approach: epoxidation followed by ii ring-opening reaction. Lipase enzyme produced by Candida antarctica (Novozyme 435) and immobilized on acrylic resin was used as an unconventional catalyst for in situ epoxidation of microbial oil. 84.55 ± 1.80% conversion was achieved after 12 hours. Novozyme 435 was found to be very stable and can be reused up to 3 cycles efficiently. In the second step, Isopropanolamine was used to open the epoxy ring with the addition of hydroxyl group. Hydroxyl value and acid number of the microbial-based polyol were found to be 299.53 ± 1.24 mg KOH/g and 4.93 ± 1.07, respectively. Fourier transform infrared spectroscopy (FTIR) and nuclear magnetic resonance (NMR) were used for structural confirmation of produced bio-polyol. Production of biobased monomers from renewable materials using enzyme catalysts can be considered clean and leads to energy saving processes. Therefore, synthesis of renewable polymers via enzymatic polymerizations of biobased monomers provides an opportunity for achieving green polymers and a future sustainable polymer industry. The production of another useful chemical, poly-γ-glutamic acid (PGA) was also studied. PGA is known to have a number of useful applications. In order to make this fermentation efficient, the detoxification of the pre-hydrolysate was carried out using a method previously developed in our lab. This detoxification method includes the combination of vacuum evaporation and solvent extraction procedures as a result of which acetic acid and hydroxy methyl furfural (HMF) were removed effectively with minimal loss of xylose. Bacillus subtilis (ATCC 23857), which is a glutamic acid-dependent strain, was used for this bioconversion. Initially, the concentration of pure xylose and L-glutamic acid were optimized by synthetic medium using response surface methodology (RSM). 65.40 g/L of xylose and 44.98 g/L of L-glutamic acid were found to be the optimal concentrations for maximum production of PGA. This strain was able to produce 12.93 ± 0.9 g/L of PGA after 96 hr of fermentation in pre-treated hemicellulose. Such studies on the production of PGA from renewable sources will contribute to further development of biorefineries and lead to commercial scale production of such products. Overall, the findings of this dissertation will contribute to the utilization of available hemicellulose streams through fully biobased processes that can lead to the development of a successful economically feasible circular bioeconomy.